Pengaruh Sarana Prasarana Pendidikan dan Kompetensi Guru Terhadap Mutu Pendidikan di Sekolah Menengah Kejuruan - Khoirul Anwar; Mochammad Hendrik; Yaredi Waruwu; Suyitno Suyitno; Citra Dewi (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
This study examines the effect of infrastructure (X1) and teacher competence on the quality of education at vocational high school-level educational institutions. This is because the quality of education is in a low position among other developed countries. This study has a purpose, namely to analyze the relationship between infrastructure and the quality of education, to analyze the influence of teacher competence on the quality of education, and to determine the effect of infrastructure and teacher competence on the quality of education. The research used is quantitative research, the data used is primary data, and the data collection technique uses survey techniques by distributing questionnaires to respondents who were selected as samples. For data analysis using multiple linear regression and the test is done using SPSS statistical tools. The results of this study obtained data that partially and simultaneously infrastructure and teacher competence have a positive and significant effect on the quality of education in vocational high schools with the infrastructure variable being the dominant variable whose influence on the quality of education is indicated by the results shown showing the t-count. > t-table that is 2,748 > 1,98896. The significance value is 0.007 <0.05, while for the significant level X2 to Y, the T-count is 2.652>T-table 1.98896 and the significance value is 0.010 <0.05.